2015
DOI: 10.1002/mnfr.201500197
|View full text |Cite
|
Sign up to set email alerts
|

Furostanolic saponins from Trigonella foenum‐graecum alleviate diet‐induced glucose intolerance and hepatic fat accumulation

Abstract: Collectively, our data suggest that fenugreek furostanolic saponins and green coffee bean extract may have potential benefits in treating insulin resistance and related conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…In both Ayurvedic and Chinese medicine, fenugreek leaves and seeds have long been known for the therapeutic efficacy in diabetes, muscle building and wrestling 1 , 7 , 21 - 25 . A number of studies have demonstrated that fenugreek attenuated body weight gain and improved insulin sensitivity 11 , 26 . The anti-diabetic efficacy of fenugreek seed extract was attributed due to the presence of furostanolic saponins and 4-hydroxyisoleucine 10 , 11 , 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both Ayurvedic and Chinese medicine, fenugreek leaves and seeds have long been known for the therapeutic efficacy in diabetes, muscle building and wrestling 1 , 7 , 21 - 25 . A number of studies have demonstrated that fenugreek attenuated body weight gain and improved insulin sensitivity 11 , 26 . The anti-diabetic efficacy of fenugreek seed extract was attributed due to the presence of furostanolic saponins and 4-hydroxyisoleucine 10 , 11 , 26 .…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated that fenugreek attenuated body weight gain and improved insulin sensitivity 11 , 26 . The anti-diabetic efficacy of fenugreek seed extract was attributed due to the presence of furostanolic saponins and 4-hydroxyisoleucine 10 , 11 , 26 . Hamden et al 28 demonstrated that administration of fenugreek seed extract to diabetic rats significantly decreased the sperm shape abnormality and improved the sperm count.…”
Section: Discussionmentioning
confidence: 99%
“…Our earlier animal studies revealed the broad-spectrum safety and anti-diabetic efficacy of fenugreek seed extract ( 28 , 29 ). In the present study, we assessed the efficacy of a novel, patented fenugreek seed extract enriched in furostanolic saponins (Fenfuro), to determine its anti-diabetic efficacy in a multicenter, placebo-controlled, double-blind, add-on clinical study in 154 diabetic subjects (male: 108; female: 46; age: 25–60 years) over a period of 90 consecutive days.…”
mentioning
confidence: 99%
“…FenfuroTM also dropped the assembly of fat and better insulin sensitivity and glucose acceptance. [53] It can be proved very useful in weight loss without any major side effect.…”
Section: Fenugreek Against Obesitymentioning
confidence: 99%